Ethnonational discourse of migrants in social networks on the example of Tajik and Kyrgyz virtual communities on VK - T. N. Yudina; D. A. Besfamilnyi (Цифровая социология)
The use of Russian-language social networks by migrants from Tajikistan and Kyrgyzstan, primarily on VK, has increased significantly in recent years. This network has enabled easy communication both within and between ethnic communities. It has become a social space of ethno-national discourse with its own laws and rules of social interaction, including conflictogenic one. At the same time, publications on ethno-national discourse of Tajik and Kyrgyz migrants in social networks are practically absent in Russian scientific literature. In this regard, the authors have set a goal to identify the features of ethno-national discourse of Kyrgyz and Tajik migrants in the VK Russian-language social network during the conflict on the Kyrgyz-Tajik border. The empirical basis of the study was the results of online questionnaire survey of 400 migrant respondents from Tajikistan and Kyrgyzstan and qualitative analysis of their posts with a vivid news agenda about the relationship between the two countries. The peculiarities of ethno-national discourse of migrants in social networks between Tajik and Kyrgyz virtual groups consisted in an attempt to understand the ongoing conflict. As a rule, the discussion has come down to finding someone to blame or calling for the cessation of hostilities. The analysis has showed that hating had been actively developing in virtual interaction between migrants. At the same time, conciliatory actions on the part of both diasporas have been observed. The results have showed the need for constant monitoring of ethno-national discourse of Tajik and Kyrgyz migrants in social networks, as virtual interaction can very likely lead to real conflicts between representatives of Tajik and Kyrgyz diasporas in Russia.